Bone marrow involvement is rare in superficial gastric mucosa-associated lymphoid tissue lymphoma. Issue 1 (January 2016) - Park, Jae Yong; Kim, Sang Gyun; Kim, Joo Sung; Jung, Hyun Chae
Abstract: Background: The initial staging work-up of gastric mucosa-associated lymphoid tissue (MALT) lymphoma includes bone marrow examination. Since gastric MALT lymphoma is mostly detected in early stages with the national cancer screening programme in Korea, bone marrow is rarely involved. Aims: To investigate the incidence of bone marrow involvement in gastric MALT lymphomas and the role of bone marrow examination for an initial staging work-up. Methods: Patients diagnosed with gastric MALT lymphoma at Seoul National University Hospital from January 2005 to July 2014 were enrolled. Clinical databases of the patients were retrospectively reviewed. Results: Out of 105 patients, 91 (86.7%) were classified as stage IE1. Among these patients, 78 patients with Helicobacter pylori infection underwent eradication therapy, and complete remission was achieved in 74 cases (94.9%). Twelve out of 13 patients (92.3%) without H. pylori infection underwent radiotherapy or surgery and all achieved complete remission. Bone marrow involvement was proven in only one patient (1.0%). Conclusion: Bone marrow involvement was rare in patients with only superficial gastric MALT lymphoma without extragastric invasion. Further studies are warranted to identify the risk factors of bone marrow involvement in gastric MALT lymphoma.